INNOVATION AND ENTREPRENEURSHIP PERFORMANCE IN ABA, ABIA STATE, NIGERIA - Kenneth Nduka Omede; Aghanenu Aghanenu (Universitas Nusa Cendana, 2021)
This study examined the influence of innovation on the performance of entrepreneurship in Aba, Abia State, Nigeria. Three hypotheses were formulated to ascertain whether or not there is significant relationship existing between the two intervening variables i.e. innovation and entrepreneurship performance in Aba, Abia State. Survey research design was adopted, while data were obtained through structured questionnaire and analyzed using Pearson’s product-moment coefficient of correlation. From the analysis, the result showed that there is an existing relationship between innovation and performance of entrepreneurship. Based on the findings it was concluded that for entrepreneurship to stand the test of time in the face of escalating competition in the emerging economies like Nigeria, premium must be placed on formulating and developing innovative culture aimed at encouraging employees to bring on board innovative ideas and strategies capable of providing innovative product and services to the customers with valued and satisfying benefits better than competitors to enhance performance and productivity. The study therefore, recommended among others that entrepreneurship policies and program should be designed in ways that addresses horizontal concerns and which generates better and viable inducement for innovation activities. Keywords: Innovation, Inducement, Entrepreneurship, Emerging Economy, Innovative Culture